12x=4(6x+18)

Simple and best practice solution for 12x=4(6x+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x=4(6x+18) equation:


Simplifying
12x = 4(6x + 18)

Reorder the terms:
12x = 4(18 + 6x)
12x = (18 * 4 + 6x * 4)
12x = (72 + 24x)

Solving
12x = 72 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
12x + -24x = 72 + 24x + -24x

Combine like terms: 12x + -24x = -12x
-12x = 72 + 24x + -24x

Combine like terms: 24x + -24x = 0
-12x = 72 + 0
-12x = 72

Divide each side by '-12'.
x = -6

Simplifying
x = -6

See similar equations:

| m^2-7m-120= | | 0=-7x^2+8x+10 | | 7n^2+35n-168=0 | | x(2x+1)=0 | | 3x-9=6x-14 | | 0=-16t^2+24t | | x(2x+x)=0 | | b^2+3b-40=0 | | 2(-18)+4=-12 | | 8x-6=2x+4 | | 80=x(x-4) | | -10x=-940 | | 6x-6=-4 | | 0.3x=9.2 | | 9+3(-2t-5)=6 | | 2=8+6p | | -0.2x+0.4x+2=-4 | | 0.30x+0.75(10)=0.15(120) | | 5(n-3)=10 | | 0.40x+0.05(180)=0.20(49) | | y=x^2+3x+14 | | 6x-(5-2x)+9=4(x-2) | | 9x^2=1 | | -4y+12=-2(3y+3) | | -17+62=-5(x+1) | | -x-0.34=4.5 | | -5(-12+12k)+8(10k-2)=7k+2k | | 4(4x-3)+10=-1 | | 8-(3q+4)=6-9 | | 3(3x+1)=2x-6x | | 8x-x^2=16 | | 3(x+1)=5-2(3x-4) |

Equations solver categories